A Sociolinguistic Analysis of Code-Mixing in Cinta Laura and Maudy Ayunda’s Utterance on Puella Id Podcast - Eva Meidi Kulsum; R. Rahil Putri Al-Hamzah; Ayang Winda Sri Widianingsih (UIN Sunan Gunung Djati Bandung, 2024)
The purpose of this research was to describe the types of code-mixing and the reason for using the code-mixing in social interaction as a sociolinguistic analysis. It employed a descriptive qualitative method through video observation and script analysis that were transcribed from the selected YouTube video. These data collection techniques aimed to collect more information by observing the participant, and the scope that researcher needed to involve in the research. The data collection procedure for this study has been divided into numerous stages. At first, watched the video. Second, created a script by transcribing the utterances. Additionally, filtered out the statements that engaged in code-mixing. In order to make the data systematic and simpler to analyze, and finally arranged it into tables. Based on the findings, it can be concluded that all three types of code-mixing proposed by Hoffmann (2014) were employed, including: intra sentential code-mixing with the 76,47% percentage, 7,35% percentage of intra lexical code-mixing, and involving a change of pronunciation which accounted for 16,17% of the total. Additionally, this study found four reasons of code-mixing; talking about a particular topic, being emphatic or emotional about something, repetition used for clarification, and expressing group character.